2018
DOI: 10.1186/s12974-018-1304-4
|View full text |Cite
|
Sign up to set email alerts
|

Microglia prevent peripheral immune cell invasion and promote an anti-inflammatory environment in the brain of APP-PS1 transgenic mice

Abstract: BackgroundUndoubtedly, neuroinflammation is a major contributor to Alzheimer’s disease (AD) progression. Neuroinflammation is characterized by the activity of brain resident glial cells, in particular microglia, but also by peripheral immune cells, which infiltrate the brain at certain stages of disease progression. The specific role of microglia in shaping AD pathology is still controversially discussed. Moreover, a possible role of microglia in the interaction and recruitment of peripheral immune cells has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 98 publications
(126 reference statements)
5
96
0
1
Order By: Relevance
“…In the same manner, PLX5622 increased viral load and enhanced mortality in a number of murine models of viral infection (32)(33)(34). A similar protective role of microglia was also apparent in the progression of neurodegeneration in APP-PS1 transgenic mice (35), the extent of excitotoxic injury in a model of brain injury induced by cerebral ischemia (36) and the dopaminergic neurotoxicity of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyrine (MPTP)(37).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the same manner, PLX5622 increased viral load and enhanced mortality in a number of murine models of viral infection (32)(33)(34). A similar protective role of microglia was also apparent in the progression of neurodegeneration in APP-PS1 transgenic mice (35), the extent of excitotoxic injury in a model of brain injury induced by cerebral ischemia (36) and the dopaminergic neurotoxicity of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyrine (MPTP)(37).…”
Section: Discussionmentioning
confidence: 68%
“…However, experiments carried out with PLX5622 and PLX3397 revealed no sex differences in the extent of microglia depletion induced by either of these treatments (31,35,(54)(55)(56)(57). In the same manner, female and male Cx3cr1-Dtr rats were found to respond identically to diphtheria toxin administration in terms of microglia depletion and body weight loss (15).…”
Section: Discussionmentioning
confidence: 84%
“…Noteworthy, an immunomodulatory effect of MSC‐EVs on macrophages has been described by Agudelo et al 96 Along with microglia and macrophages, a certain amount of other cells derived from blood can contribute to the inflammatory response that characterizes the AD brains. In fact, neutrophils, T cells, and B cells could cross the damaged blood brain barrier (see, eg, Reference 97), thus contributing to the exacerbation of central inflammation. Indeed, activation of circulating peripheral immune cells is observed in patients with early stages of AD 98‐100 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dagher et al (2015) showed a positive effect on cognitive behaviors using the PLX5622 diet in 15-month-old 3xTg-AD mice, but with no effect on plaque burden or plaque size. Subsequently, Unger et al (2018) reported that in 12-month-old APP-PS1 transgenic mice that also have significant levels of amyloid burden and fed with PLX5622 diet, there was neither an impact on plaque burden, nor cognition. The differences in behavioral outcomes reported in the two mouse models could easily be explained by contrasting experimental protocols in each study, and influences of housing conditions, animal gender, and age and feeding (Gemma and Bachstetter, 2013).…”
Section: Discussionmentioning
confidence: 99%